Foundations of Effective Learning Through Educational Practices - Juran Carloses Rodríguez; Emily Thore Turner; Antonio Reyes Gonzales; Ashleighe Thompson; Yifan Zhang Shu (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
Effective learning is key to developing competent students who are ready to face global challenges. Effective learning practices rely not only on proper educational theories but also on relevant pedagogical approaches and an understanding of factors influencing the learning process. This study aims to explore the foundations of effective learning by analyzing various learning theories, pedagogical approaches, and the factors that support learning success. The study employs a library research methodology, analyzing literature from reliable sources such as journals, books, and academic articles, discussing learning theories and best practices in education. The data is analyzed descriptively to identify key concepts underlying effective learning. The findings suggest that effective learning is grounded in the application of learning theories such as constructivism, behaviorism, and cognitivism. Additionally, pedagogical approaches like problem-based learning, collaborative learning, and project-based learning have proven effective in enhancing students' critical thinking and social skills. Internal factors such as motivation and cognitive ability, as well as external factors like family support and educational facilities, also significantly impact learning. The use of technology as a supporting tool further enhances learning effectiveness when used wisely and in alignment with learning objectives.